Intercropping switchgrass with hybrid poplar increased carbon sequestration on a sand soil. (July 2020) - Collins, H.P.; Kimura, E.; Polley, W.; Fay, P.A.; Fransen, S.
Abstract: Switchgrass ( Panicum virgatum ) has been identified as an important source of cellulosic biomass to produce biofuels and improve soil carbon storage. The natural 13 C abundance of soils was used to calculate the quantity and turnover of C in a hybrid poplar ( Populus x generosa and P. x canadensis ) plantation intercropped with switchgrass. Levels of intercrop were grass cultivars inter-planted with poplar trees (IC), monoculture switchgrass (SM) and monoculture hybrid poplar (PM). Four years of intercropping increased soil organic carbon (SOC) 18% in the surface 60 cm for switchgrass. Surface soil was enriched 1.5‰ δ 13 C cropped to switchgrass compared to the poplar monoculture. On average, 14% of SOC in SM was derived from switchgrass and 9% in IC. SOC accrual rates were 0.32 Mg C ha −1 yr −1 for the poplar monoculture; 1.3 Mg C ha −1 yr −1 for switchgrass monocultures and 1.0 Mg C ha −1 yr −1 for intercrop. The CO2 evolved during laboratory incubations was used to determine the size and turnover of the functional C pools of SOC. SOC was divided into three functional pools: an active, slow and resistant pool; where the size and turnover rates were estimated by curve fitting using a three-component first-order model. The resistant C pool was 62%, slow (Cs ) 34% and active (Ca ) 4% of SOC. The Cs increased 31% in the 0–15 cm horizon of SM and IC compared to PM. Field mean resident times of Ca and Cs cropped to switchgrass were 50d and 15yr for surface soil, respectively, compared to 41d and 9yr for PM. Switchgrass intercropped with hybrid poplar increased SOC compared to poplar alone. Highlights: Four years of intercropping switchgrass and hybrid poplar increased soil organic carbon (SOC) 18% in the surface 60 cm. SOC accrual rates were 0.32, 1.3, and 1.0 Mg C ha −1 yr −1 for the poplar, switchgrass monocultures and intercrop, respectively. Field mean resident time of soil C-pools increased under the intercropping system compared to poplar monocultures. Switchgrass production for bioenergy will increase SOC in soils low in SOC in a relatively short time period.